Padronização de normas de biossegurança em laboratórios de engenharia bioquímica aplicando lean six sigma - Marins, João Paulo Lobo (Universidade Federal de São Carlos, 2021)
This article historically contextualizes the biosafety standards necessary for safe work in biochemical engineering laboratory environments. The Lean Six Sigma methodology was used to raise the main pains of professionals working at LaFaC and LaDABio and, after that, define the focus problem to be standardized and improved. It was determined that the absence of complete training, easily accessible, without an adequate format or established recurrence would be the chosen problem for the application of the phases of the DMAIC tool. After online surveys and interviews with master's students, doctoral students and student-researchers of these sectors, the minimum requirements for a training path desired by users were detailed and also what currently are the main existing sources of failure. More information was collected in other stages, such as, for example, the Ishikawa Diagram, the Cause and Effect Matrix and the SIPOC. From statistical analyses, such as the Multi-Vari Chart and the 2-proportions test in the Minitab® computer program, the influence of the laboratories on the defects found was analyzed. With this information in hand, the present study built an implementation plan for the suggested improvements, including forms to assess the quality of new training to be created, an accessible storage location and an already defined recurrence.
Standardization of biosafety rules in biochemical engineering laboratories applying lean six sigma
Keywords: Engenharia bioquímica; Biossegurança; Lean; Six sigma; DMAIC; Otimização de processos; Treinamentos de biossegurança; Organismos geneticamente modificados; Biosafety; Biochemical engineering; Process optimization; Biosafety training; Genetically modified organisms; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA; ENGENHARIAS